NBGNU: a hypoxia-activated tripartite combi-nitrosourea prodrug overcoming AGT-mediated chemoresistance. (18th December 2018) - Ge, Yao; Lai, Xinxin; Li, Jintao; Yu, Ran; Zhuang, Zhuochen; Sun, Guohui; Cui, Xin; Zhang, Na; Zhao, Lijiao; Upadhyaya, Pramod; Zhong, Rugang
Aim: A hypoxia-activated combi-nitrosourea prodrug, N -(2-chloroethyl)- N ′-2-(2-(4-nitrobenzylcarbamate)- O 6 -benzyl-9-guanine)ethyl- N -nitrosourea (NBGNU), was synthesized and evaluated for its hypoxic selectivity and anticancer activity in vitro .Results: The prodrug was designed as a tripartite molecule consisting of a chloroethylnitrosourea pharmacophore to induce DNA interstrand crosslinks (ICLs) and an O 6 -benzylguanine analog moiety masked by a 4-nitrobenzylcarbamate group to induce hypoxia-activated inhibition of O 6 -alkylguanine-DNA alkyltransferase. NBGNU was tested for hypoxic selectivity, cytotoxicity and DNA ICLs ability. The reduction product amounts, cell death rates and DNA ICL levels induced by NBGNU under hypoxic conditions were all significantly higher than those induced by NBGNU under normoxic conditions.Conclusion: The tripartite combi-nitrosourea prodrug exhibits desirable tumor-hypoxia targeting ability and abolished chemoresistance compared with the conventional chloroethylnitrosoureas.